Proceso de geocodificación de direcciones en la ciudad de Medellín, una técnica determinística de georreferenciación de direcciones (2013)
This article is a comparative empirical study of different geocoding processes performed in the Municipality of Medellin for the georeferencing of primary information in all processes of Governance and Territorial Development, which are the support for decision-making and planning of public resources. Among the processes to be analyzed we have deterministic and probabilistic methods which allow, through the standardization and regulation of addresses, a result framed in a space environment that meets quality standards for both the success percentage of found addresses and positional accuracy of the result, which are used for different types of spatial analysis in Security, Territorial Planning, Welfare, Road Infrastructure, Health, Land Registry, Environment, Education, Assistance to victims of conflict and RGCAs (requests, grievances, complaints and applications).